E-learning in physical education learning: How are students' perceptions during the COVID-19 pandemic? - Maulana Mansur; Irfan Zinat Achmad; Ruslan Abdul Gani (UIR Press, 2022)
In implementing e-learning, it demands readiness from the school as well as from its students, the most basic obstacle is the lack of communication media used by students and limited signals that affect students’ perceptions of physical education learning during the Covid-19 pandemic. This study aims to determine how big the perception of class VIII SMPN 2 Cariu is in learning physical education during the Covid-19 pandemic. This research is a quantitative descriptive research, the method used is a survey. Data collection techniques in the form of a questionnaire using a Likert scale test. The population used was class VIII SMPN 2 Cariu, totaling 97 students consisting of 50 male students and 47 female students. The sample used in this study were 97 students with a non-probability sampling technique and a saturated sampling technique. The data in the study were analyzed using descriptive statistics with percentages. The results showed that student’s perception of class VIII SMPN 2 Cariu in learning physical education in the new normal era was overall in the